Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea) - Ruta, Rafał (Zootaxa, 2019)
A new genus of Scirtidae, Calvariopsis gen. nov., is described to accommodate two species described by Maurice Pic (Prionocyphon brasiliensis Pic, 1916 and Cyphon sculptipenne Pic, 1931) and 14 newly described species: Calvariopsis bituberculata sp. nov. (French Guiana), C. borowieci sp. nov. (Ecuador), C. fourgassiense sp. nov. (French Guiana), C. guyanense sp. nov. (Guyana), C. kawense sp. nov. (French Guiana), C. nana sp. nov. (Brazil), C. panamense sp. nov. (Panama), C. peruviana sp. nov. (Peru), C. picta sp. nov. (Bolivia), C. pittieri sp. nov. (Venezuela), C. saopaulense sp. nov. (Brazil), C. venezuelense sp. nov. (Venezuela), C. wittmeri sp. nov. (Brazil), and C. yanayacuense sp. nov. (Ecuador) [type species of Calvariopsis]. The new genus can be distinguished from other Neotropical Scirtidae on the basis of the following characters: antennae filiform, subgenal ridge without buttonhole configuration, head with deep subantennal grooves, mesoventral process short, as long as wide or shorter, hind legs not saltatorial.